Resource allocation for remote desktop sessions in Utility Grids - Talwar, Vanish; Agarwalla, Bikash; Basu, Sujoy; Kumar, Raj; Nahrstedt, Klara (Concurrency and computation, 2006)
Emerging large‐scale utility computing systems such as Grids promise computing and storage to be provided to end users as a utility. System management services deployed in the middleware are a key to enabling this vision. Utility Grids provide a challenge in terms of scale, dynamism and heterogeneity of resources and workloads. In this paper, we present a model‐based architecture for resource allocation services for Utility Grids. The proposed service is built in the context of interactive remote desktop session workloads and takes application performance QoS models into consideration. The key design guidelines are hierarchical request structure, application performance models, remote desktop session performance models, site admission control, multi‐variable resource assignment system and runtime session admission control. We have also built a simulation framework that can handle mixed batch and remote desktop session requests, and have implemented our proposed resource allocation service into the framework. We present some results from experiments using the framework. Our proposed architecture for resource allocation services addresses the needs of emerging utility computing systems and captures the key concepts and guidelines for building such services in these environments. Copyright © 2005 John Wiley & Sons, Ltd.